Pengaruh Segmentasi Pasar dan Positioning Terhadap Keputusan Pembelian Simcard Axis di Kota Padang - Gita Remeo Nensi; Rose Rahmidani (Jurnal Ecogen, 2019)
This study aims to determine how much influence the market segmentation and positioning to purchase decision of the simcard Axis in Padang city. This type of research is causative. The population in this study were peoples in Padag city. The sample were takrn using Cochran formula with 100 respondents. This sampling technique used is based on nonprobability sampling method. The type of data used in this study is primary data. Data analysis technique used multiple regression analysis technique using SPSS version 24.00. The results of this study indicate that: 1) Market segmentation has a positive significant effect on decision purchase simcard Axis in Padang city. 2) Positioning has a positive significant effect on decision purchase simcard  Axis in Padang city.  Keyword: market segmentation simcard axis, positioning simcard axis, purchase decision simcard axis